The Problem of Ideological Approaches to Authoritarian Regimes: The Case of Hungary and Fidesz - ERGUN, İlteriş (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study examines the ideological foundations of Viktor Orbán’s Fidesz Party, challenging prevailing interpretations that describe Hungary’s political transformation since 2010 as merely a case of pragmatic authoritarianism or electoral manipulation. While much of the literature attributes Fidesz’s repeated electoral success to institutional asymmetries and illiberal regime structures, this paper argues that the party’s endurance and popular legitimacy stem from the consolidation of a coherent ideological framework: nationalist conservatism. Drawing on recent scholarship and Fidesz’s intellectual networks, the study situates the Orban regime within a broader global movement that seeks to replace neoliberal universalism with communitarian and paternalistic values grounded in nation, family, and faith. It analyzes how the regime has developed an ideological synthesis—combining illiberal conservatism, civilizational ethnocentrism, and paternalist populism—that functions as a counter-hegemonic alternative to liberal democracy. By exploring the intellectual lineage from thinkers such as Roger Scruton and Yoram Hazony, the paper demonstrates that Hungary has become both the laboratory and exemplar of a new nationalist-conservative ideology shaping right-wing politics globally. Thus, Fidesz’s case illustrates the limits of ideologically neutral explanations of authoritarianism and underscores the need to reexamine the role of ideology in sustaining contemporary illiberal regimes.